RACK1 Acts as a Potential Tumor Promoter in Colorectal Cancer. (10th March 2019) - Li, Xue-Yang; Hu, Yi; Li, Nian-Shuang; Wan, Jian-Hua; Zhu, Yin; Lu, Nong-Hua
Abstract : Background . The receptor of activated protein kinase C 1 (RACK1) promotes the progression and invasion of several cancers. However, the role of RACK1 in the pathogenesis of colorectal cancer (CRC) has not been clearly defined. Herein, we aimed to investigate the biological role of RACK1 in CRC. Materials and Methods . The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) dataset were searched, and the expression of RACK1 in CRC tissues and adjacent normal tissues was evaluated. Immunohistochemical staining was performed to detect the expression of RACK1 in human CRC, adenoma, and normal tissues. Western blotting was used to detect the expression of RACK1 in human CRC cell lines. Functional assays, such as BrdU, colony formation, and wound healing and transwell invasion assays, were used to explore the biological role of RACK1 in CRC. Results . RACK1 was upregulated in CRC tissues compared with its expression in adjacent normal tissues in TCGA and the GEO dataset (P < 0.05 ). Moreover, RACK1 was significantly overexpressed in CRC and adenoma tissues compared with its expression in normal tissues (P < 0.05 ). Loss-of-function experiments showed that RACK1 promoted cell proliferation, migration, and invasion in vitro . Conclusions . Our data indicated that RACK1, as an oncogene, markedly promoted the progression of CRC, which suggested that RACK1 is a potential therapeutic target for CRC management.